Enhanced adsorption of Pb(II) by phosphorus‐modified chicken manure and Chinese medicine residue co‐pyrolysis biochar. Issue 11 (23rd July 2022) - Chen, Xi; Zhu, Xiaoxuan; Fan, Guangjian; Wang, Xu; Li, Haibo; Li, Hui; Xu, Xinyang
Abstract: The pollution of lead (Pb (II)) to water resources is becoming more and more serious. It is always a difficult problem to find efficient and low‐cost adsorbents. Chicken manure (CM) and Chinese medicine residue (CMR) were modified with potassium dihydrogen phosphate (KH2 PO4 ) and pyrolyzed to obtain a modified material (PBC) for the treatment of Pb(II) in an aqueous solution. A variety of characterization analysis results could prove that KH2 PO4 was successfully introduced to PBC. By adjusting the initial pH, the zeta potential of PBC varies from −3.2 to −43.1 mV, it could be seen that PBC had excellent applicability in the broad range pH value (1.0–6.0). Experimental and model results showed that R 2 of the pseudo‐first order kinetic model and the pseudo‐second order kinetic model are greater than 0.99, indicating that that physical and chemical adsorption played a significant role in Pb(II) removal by PBC. An adsorption isotherm analysis showed that the adsorption capacity n in this study is greater than 1, confirming that PBC has a good adsorption effect on Pb (II). R 2 of the Langmuir model of PBC is 0.981, and its maximum adsorption capacity of Pb(II) could reach 599.4 mg/g. Environmentally friendly PBC could be used as an effective adsorbent to remove Pb(II) from aqueous systems. Research highlights: Chicken manure and Chinese medicine residue were converted into biochar to improve utilization. The modified biochar exhibited extraordinary Pb(II) adsorption capacity. Adsorption mechanisms: Surface complexation, ions exchange, coprecipitation, and so on. Remained great Pb(II) removal efficiency at different pH and Pb(II) concentration. Abstract : The main mechanisms of lead adsorption by PBC